HUBUNGAN FASILITATOR DENGAN PELAKSANAAN GOOD PHARMACY PRACTICE (GPP) DI APOTEK DENPASAR - Putu Satrya, Dewa Ayu; Arimbawa, Putu Eka; Jaelani, Abdul Khodir (Jurnal Endurance, 2017)
Pharmaceutical service is said to be good if it meets the criteria of Good Pharmacy Practice (GPP) which is patient oriented or often called pharmaceutical care. GPP implementation on community pharmacy proved to be slower than expected, although many pharmacists have agreed with the GPP concept. The purpose of this research is to accelerate the achievement of GPP by applying the facilitator which has high influence on pharmacist attitude in GPP implementation, so as to improve the quality assurance of pharmaceutical service in community pharmacy. GPP implementation also aims to improve the quality of patients, because the service focus on the patient or often known as patient oriented. The research method used cross sectional survey design. Quantitative data with questionnaires were taken prospectively for patients. The sampling technique used is random sampling to 70 pharmacists in charge of pharmacies in pharmacies of Denpasar City Bali. The result of the research shows the influence of facilitator to GPP implementation in Apotek Denpasar-Bali. The attitudes of facilitators in the implementation of the influential GPP in this study were Doctor Relationship with Pharmacist (p = 0,010), Human Resources (p = 0,023), and teamwork (p = 0.012) had a positive and significant effect on pharmacist attitude in GPP implementation. The facilitator variable of physician and pharmacist relationship is the most influential variable (r = 0,340) on pharmacist attitude in implementing Good Pharmacy Practice (GPP).